Spatial Resolution in SPECT: Influence of Measurement Set-Up and Reconstruction Parameters - Geworski, L.; Jordan, K. (Nuklearmedizin - NuclearMedicine, 1991)
The ability of a tomographic system to detect small lesions and to assess them quantitatively is affected by several performance parameters, among them spatial resolution in the transverse slice and in the axial direction. This study was done to determine reconstructed resolution under clinical conditions for various parameters, i. e. radius of rotation, radial position within the transverse field of view, and amount of smoothing in the reconstruction process (various reconstruction filters and a Metz prefilter). The axial resolution is independent of the reconstruction filter but depends on the prefilter, the radius of rotation (ROR), and the source position. The transaxial resolution is dependent on the reconstruction filter, the prefilter, the ROR, and the source position. The reconstructed resolution and the system resolution were compared and differences between both are discussed.Die Fähigkeit eines tomographischen Systems, kleine Läsionen nachzuweisen oder quantitativ zu bestimmen, hängt von verschiedenen Leistungsparametern ab, unter anderem von der räumlichen Auflösung innerhalb der transversalen Schicht und in axialer Richtung. Unter patientenbezogenen Bedingungen wird die rekonstruierte Auflösung bestimmt in Abhängigkeit vom Rotationsradius, der radialen Position im Gesichtsfeld und vom Grad der Datenglättung im Rekonstruktionsprozeß (unterschiedliche Rekonstruktionsfilter, zweidimensionale Metz-Prefilter). Die axiale und transversale Auflösung ist abhängig von Prefilter, Rotationsradius (ROR) und Quellenposition. Die transversale Auflösung ist zusätzlich vom Rekonstruktionsfilter abhängig. Der Vergleich der transversalen Auflösung und der Systemauflösung – für einen dem ROR entsprechenden Meßabstand gemessen – wird diskutiert.